DIRECTIONS AND MEANS OF IMPROVING WORK MOTIVATION IN THE PERSONNEL MANAGEMENT SYSTEM OF ENTERPRISES IN CONDITIONS OF INSTABILITY (Development Service Industry Management, 2024)
The article emphasizes the issues of preserving the personnel potential of domestic enterprises in conditions of instability. It is noted that work motivation is currently one of the leading factors in maintaining personnel at enterprises in situations where the demand for labor significantly exceeds the supply of labor. It was established that the labor shortage situation in the labor market of Ukraine was formed due to mass external migrations of the population during the war, significant internal displacements of the population, large volumes of educational external migration that have become characteristic over the last few years, mobilization and other factors.The purpose of the study is to substantiate the directions and means of improving the labor motivation system at domestic enterprises in conditions of instability. The directions, factors and tools of the policy for improving the labor motivation system at enterprises are determined.It was concluded that staff retention is closely correlated with pay and incentives, in other words, work motivation. The strategic priorities of the policy of improving the system of motivating the personnel of domestic enterprises in conditions of instability should be: improving the quality of the system of financing professional training and improving the qualifications of personnel; improvement of planning of costs for motivation, retention and development of personnel; improvement of resource provision of the system of motivation and stimulation of the work of personnel; development of entrepreneurial activity of personnel; increasing the efficiency of the functioning of the infrastructure elements of the personnel motivation system; growth of costs for intellectualization of business processes, increase and effective use of intellectual capital of the enterprise.    It is shown that further scientific research in this direction relates to the improvement of the methodology of analyzing the social responsibility of entities in the field of consumer services.
Keywords: personnel; management; personnel management; work motivation; business development; instability